2005
DOI: 10.1158/1078-0432.ccr-04-0738
|View full text |Cite
|
Sign up to set email alerts
|

Steroid 5α-Reductase Isozymes I and II in Recurrent Prostate Cancer

Abstract: Purpose: Prostate cancer recurs during androgen deprivation therapy despite reduced circulating androgens. We showed that recurrent prostate cancer tissue has testosterone levels similar to androgen-stimulated benign prostate, whereas dihydrotestosterone levels were reduced 82% to 1.45 nmol/L, sufficient for androgen receptor activation. The altered testosterone/dihydrotestosterone ratio in recurrent prostate cancer suggests loss of 5a-reducing capability. The aim of this study was to characterize steroid 5a-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
117
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 48 publications
10
117
1
4
Order By: Relevance
“…AICaP samples were obtained from transurethral resection specimens from men with urinary retention from local recurrence during androgen deprivation. ADCaP and BPH samples were obtained from prostatectomy specimens from men with localized prostate cancer (26). Tissue procurement and studies were performed with approval by the University of North Carolina at Chapel Hill Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…AICaP samples were obtained from transurethral resection specimens from men with urinary retention from local recurrence during androgen deprivation. ADCaP and BPH samples were obtained from prostatectomy specimens from men with localized prostate cancer (26). Tissue procurement and studies were performed with approval by the University of North Carolina at Chapel Hill Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Prostate growth in normal and neoplastic conditions requires the intraprostatic conversion of testosterone to dihydrotestosterone (DHT) by 5α-reductase isozymes (4,5). The 4-azasteroid finasteride [17ß-(N-t-butylcarbamoyl)-4-aza-5α-androst-1-en-3-one] is a 5α-reductase inhibitor to be clinically approved for use in men for the treatment of human benign prostatic hyperplasia (BPH) and prostate cancer (PC) (6)(7)(8)(9). These clinical applications are based on the ability of finasteride to inhibit the type II isoform of the 5α-reductase enzyme, which is the predominant form in human prostate, although type I isoform is also expressed (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…56 These findings were corroborated by Page et al, 57 who demonstrated after shortterm LH-RH-agonist exposure, that intraprostatic T-and DHT levels remained at 20-30% of control values. Titus et al 58 also demonstrated a shift of expression and isoenzyme activity of 5a-R2 towards 5a-R1 in recurrent prostate cancer. Thus dual inhibition of these isoenzymes might retard the progression of recurrent prostate cancer.…”
Section: Chemoprevention Of Prostate Cancermentioning
confidence: 90%